1996
DOI: 10.1016/s0735-1097(96)00271-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine in Pathogenesis of Syndrome X: Assessment With Coronary Hemodynamic Measurements and Thallium-201 Myocardial Single-Photon Emission Computed Tomography

Abstract: Patients with syndrome X with abnormal exercise scintigrams have high susceptibility to myocardial ischemia during exercise or pharmacologic stress tests, probably owing to reduced coronary flow reserve. A heterogeneous response to endogenous adenosine may contribute to scintigraphic perfusion abnormalities and myocardial ischemia during exercise in this subset of patients with syndrome X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Then, 50 g of acetylcholine was injected into the right coronary artery, followed by angiography. At baseline and acetylcholine-induced coronary spasm or 1 min after the maximum dose of acetylcholine was injected into the left coronary artery, paired samples of 2 ml of blood were collected simultaneously from the main trunk of the left coronary artery and coronary sinus to measure the myocardial lactate extraction rate, as reported previously (20).…”
Section: Abbreviations and Acronymsmentioning
confidence: 99%
“…Then, 50 g of acetylcholine was injected into the right coronary artery, followed by angiography. At baseline and acetylcholine-induced coronary spasm or 1 min after the maximum dose of acetylcholine was injected into the left coronary artery, paired samples of 2 ml of blood were collected simultaneously from the main trunk of the left coronary artery and coronary sinus to measure the myocardial lactate extraction rate, as reported previously (20).…”
Section: Abbreviations and Acronymsmentioning
confidence: 99%
“…Furthermore, the present study showed that the transcardiac gradient of plasma VEGF levels was decreased in the patients with cardiac syndrome X compared to the control subjects. Although pathogenic mechanism for cardiac syndrome X remains unclear, endothelium-dependent and/or-independent vasomotor dysfunction in resistance coronary arteries has been reported to play a pathogenetic role in this disease [13][14][15][16]. In fact, the present patients with cardiac syndrome X also had a blunted response of myocardial blood flow to ACh.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, the decrease in myocardial production of VEGF may represent an underlying mechanism for the functional and structural abnormalities of coronary microcirculation in some patients with cardiac syndrome X, although cardiac syndrome X has extremely heterogeneous mechanisms [14][15][16]. Another feature of cardiac syndrome X is an enhanced cardiac pain perception [13][14][15][16]. Although the cause of the neural abnormality in cardiac syndrome X is also poorly understood, it is worth noting that VEGF has direct neuro-protective effects [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is added to a predisposition of vulnerable vessels (coronary hypersensitivity). However, the exact mechanism of coronary vasospasm is still unclear [7,8]. The role of the autonomic nervous system is controversial.…”
Section: Discussionmentioning
confidence: 99%